PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KEMUNGKINAN TERJADINYA FINANCIAL DISTRESS (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2011-2020) - Patricia Graciella Wilhelmina Pardede; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of ownership structure on the possibility of financial distress in manufacturing companies listed on the Indonesia Stock Exchange in 2011-2020. This study uses the dependent variable (Financial Distress), independent variables (Institutional Ownership, Insider Ownership, Foreign Ownership and Government Ownership), and control variables (Company Size, Net Profit Margin, Payment Ratio, Leverage and Sales Growth). The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2011-2020. By using purposive sampling in sample selection, 160 research samples were obtained for 10 consecutive years (2011-2020). Testing the hypothesis of this study using multiple regression analysis and logistic regression analysis. The findings of this study reveal that institutional ownership and the possibility of financial distress are negatively and significantly correlated, insider ownership and the possibility of financial distress are positively and significantly correlated, foreign ownership and the possibility of financial distress are negatively and significantly correlated, and government ownership and the possibility of financial distress. distress is negatively correlated and not significant.